Freeze Core Sampling to Validate Time‐Lapse Resistivity Monitoring of the Hyporheic Zone. Issue 4 (4th October 2012) - Toran, Laura; Hughes, Brian; Nyquist, Jonathan; Ryan, Robert
<x xml:space="preserve">Abstract</x> A freeze core sampler was used to characterize hyporheic zone storage during a stream tracer test. The pore water from the frozen core showed tracer lingered in the hyporheic zone after the tracer had returned to background concentration in collocated well samples. These results confirmed evidence of lingering subsurface tracer seen in time‐lapse electrical resistivity tomographs. The pore water exhibited brine exclusion (ion concentrations in ice lower than source water) in a sediment matrix, despite the fast freezing time. Although freeze core sampling provided qualitative evidence of lingering tracer, it proved difficult to quantify tracer concentration because the amount of brine exclusion during freezing could not be accurately determined. Nonetheless, the additional evidence for lingering tracer supports using time‐lapse resistivity to detect regions of low fluid mobility within the hyporheic zone that can act as chemically reactive zones of importance in stream health.